Corporate hedging under personal and corporate taxation - Noe, T; Kale, J (1990)
Researchers have argued that financial distress costs and corporate tax shields can induce value-maximizing corporations to hedge their operating cash flows. We demonstrate that, for a fixed level of debt in the capital structure, the presence of personal income taxation and corporate non-debt tax shields may cause hedging to lower the value of the firm. When the hedging decision is evaluated at the optimal capital structure, hedging increases firm value.